Analysis of food literacy dimensions and indicators: A case study of rural households - Zareimanesh, Bahareh; Namdar, Razieh (Frontiers in Sustainable Food Systems, 2022)
Food has always been the focus of much discussion due to its value and importance in human life. Policymakers use the idea of food literacy as a solution to population and environmental health and food security. Two objectives were considered in this research: investigating food literacy construct validity and reliability and also analyzing five dimension that reflect food literacy scale. The present research is a survey and the statistical population is rural households in Dashti County of Bushehr province. The number of statistical populations was determined by Cochran's formula 232 households. They were selected by stratified multi-stage random sampling method. Based on the results and fitness indicators, it was determined that the research factor analysis model based on the five dimensions of food literacy (social, economic, health, skills, environmental and welfare of farm animals) has suitable and acceptable measures (RMSEA = 0.065). Evidence from this study has shown that creating an effective link to promoting the indigenous and local foods and food production process is effective in promoting food diversity, food literacy and food security in rural communities. There is little research that considers food literacy indicators empirically, based on the proposed model, the selected constructs of the research had examined food literacy indices in rural communities. The results of cluster analysis showed that most studied groups classified in the average level in terms of food literacy and had the highest average in the social index of food literacy. The results of this study can help to perception and further professionalize and exploit opportunities to promote food literacy and provide guidance for planners and other stakeholders working in food security and sustainable development.